2021
DOI: 10.3389/fcell.2021.705060
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation as a Potential Therapeutic Target for Checkpoint Inhibitors: A Comprehensive Analysis of Immune Microenvironment in BRAF Mutated Colon Cancer

Abstract: BRAF mutated colon cancer presents with poor survival, and the treatment strategies are controversial. The tumor microenvironment, which plays a key role in tumorigenesis as well as responses to treatments, of this subtype is largely unknown. In the present study, we analyzed the differences of immune microenvironments between BRAF mutated and BRAF wild-type colon cancer utilizing datasets from The Cancer Genome Atlas and Gene Expression Omnibus and confirmed the findings by tissue specimens of patients. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…A recent study shows promising results of pembrolizumab in MSI-high advanced CRC [ 41 ]. A study showed that some immunotherapeutic targets were found highly expressed in BRAF mutated patients [ 42 ]. We did not have any patient treated with ICI drugs; however, our molecular data suggested significantly increased expression of CTLA4 and HAVCR2 in only MSI tumors and not in the MSS tumors, suggesting possible beneficial effects of the CTLA4 inhibitor (e.g., ipilimumab) and the HAVCR2 inhibitor in this subgroup of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows promising results of pembrolizumab in MSI-high advanced CRC [ 41 ]. A study showed that some immunotherapeutic targets were found highly expressed in BRAF mutated patients [ 42 ]. We did not have any patient treated with ICI drugs; however, our molecular data suggested significantly increased expression of CTLA4 and HAVCR2 in only MSI tumors and not in the MSS tumors, suggesting possible beneficial effects of the CTLA4 inhibitor (e.g., ipilimumab) and the HAVCR2 inhibitor in this subgroup of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor infiltrating lymphocytes (TILs) have been found in diverse cancer types, which can predict the prognosis of patients 50 . Abnormally infiltrated immune cells in tumors promote tumor growth and escape from the host 51 . Expression levels of ACADS in CRC patients were positively correlated with CD8+ T cells, which are activated by interacting with antigens presented through molecules on antigen presenting cells, playing an important role in inducing the anti-tumor immune response 52 .…”
Section: Discussionmentioning
confidence: 99%
“…However in melanoma, BRAF mutations are evidently linked to an immunosuppressive environment [89,90]. A comparison of BRAF mutant versus wild-type colorectal tumors using transcriptomics and IHC, showed more stromal cells, more immune cell infiltration, CD8+ T cell infiltration and higher expression levels of checkpoint molecule (PD-1, PD-L1, CTLA4 and LAG3) in BRAF mutant than in BRAF wild-type tumors [91]. In vitro, BRAF mutations caused an increased production of IL-8 [92].…”
Section: Braf Mutationsmentioning
confidence: 99%